2024
DOI: 10.1111/1365-2745.14247
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale facilitative effects for a single nurse shrub: Impact of the rainfall gradient, plant community and distribution across a geographical barrier

Nicolás Velasco,
Cristina Soto‐Agurto,
Lucas Carbone
et al.

Abstract: Importance of nurse plants structuring plant communities is well‐appreciated at local scales, yet the effect of a single nurse on large scales has been neglected in analyses. So far, studies only use environmental gradients within one type of ecosystem and tend to generalize the nurse effects. To assess how the effect of a single nurse species is modulated by different environmental settings, interactions between the shrub Vachellia caven and the surrounding plant communities were evaluated at 481 paired plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The study found that as precipitation levels increased to 350 mm, shrub biomass growth also increased, suggesting an optimal range for precipitation in the area. However, excessive rainfall beyond a certain threshold may lead to a shift in dominant species from shrubs to other plant types within the region, thereby impacting the growth environment of shrubs and resulting in a reduction in their abundance [94][95][96]. In terms of temperature, there was no discernible pattern of shrub biomass increase or decrease as temperature rose.…”
Section: Spatial Characteristics Of Biomass In Shrublandmentioning
confidence: 97%
“…The study found that as precipitation levels increased to 350 mm, shrub biomass growth also increased, suggesting an optimal range for precipitation in the area. However, excessive rainfall beyond a certain threshold may lead to a shift in dominant species from shrubs to other plant types within the region, thereby impacting the growth environment of shrubs and resulting in a reduction in their abundance [94][95][96]. In terms of temperature, there was no discernible pattern of shrub biomass increase or decrease as temperature rose.…”
Section: Spatial Characteristics Of Biomass In Shrublandmentioning
confidence: 97%